Pathogenesis of peritoneal high‐grade serous carcinoma after risk‐reducing surgery: a systematic review - Tamar A Gootzen; Anouk B Bouwmeester; Joanne A deHullu; Jurgen MJ Piek; Jeroen AWM van derLaak; Michiel Simons; Miranda P Steenbeek (The Journal of Pathology: Clinical Research)
Abstract Germline BRCA1/2 pathogenic variant carriers have an increased risk for high‐grade serous carcinoma (HGSC) and are therefore advised to have risk‐reducing salpingo‐oophorectomy around the age of 40. However, a risk of 0.9% to develop peritoneal HGSC remains in these women, which increases to 27.5% when serous tubal intraepithelial carcinoma (STIC) is detected. The pathophysiological mechanism that leads to the development of peritoneal HGSC after salpingectomy or salpingo‐oophorectomy is still largely unknown. In this systematic review, we aim to provide insights into the pathogenic pathways of peritoneal HGSC after salpingectomy or salpingo‐oophorectomy. Therefore, we performed a systematic search for studies investigating pathophysiological mechanisms related to peritoneal HGSC in PubMed and EMBASE. A total of 49 articles were included in this study. Most evidence was found on mechanisms following a tubal origin, such as clonality between STIC and peritoneal HGSC as well as molecular similarities between fallopian tube (FT) epithelium and peritoneal HGSC. Additionally, FT epithelium was shown to adhere to the ovary and could therefore stay present after isolated salpingectomy. There might be a role for the endometrium, as it was observed that serous endometrial intraepithelial carcinoma (SEIC) has a clonal relationship with extra‐uterine HGSC. The role of the ovary seems limited, although some mouse models show a role for follicular fluid in the dissemination of malignant cells on the peritoneum. In conclusion, different mechanisms might be responsible for peritoneal HGSC development after bilateral salpingectomy or salpingo‐oophorectomy. Most available evidence supports the dissemination of precursor cells originating in the FT. Also, a possible role for the endometrium was found. An ovarian origin seems less likely; however, execution of oophorectomy does not seem obsolete in clinical practice as follicular fluid might promote dissemination and residual tubal tissue can be present on the ovary after salpingectomy.